Humidity Sensor Systems: Perovskite‐Induced Ultrasensitive and Highly Stable Humidity Sensor Systems Prepared by Aerosol Deposition at Room Temperature (Adv. Funct. Mater. 3/2020). (17th January 2020) - Cho, Myung‐Yeon; Kim, Sunghoon; Kim, Ik‐Soo; Kim, Eun‐Seong; Wang, Zhi‐Ji; Kim, Nam‐Young; Kim, Sang‐Wook; Oh, Jong‐Min
Abstract : In article number 1907449, Nam‐Young Kim, Sang‐Wook Kim, Jong‐Min Oh, and co‐workers fabricate an ultrasensitive and highly stable humidity sensor through perovskite/ceramic nanocomposite layers using a simple and cost‐effective aerosol deposition process. The perovskite in the device with a porous structure plays an important role involving a massive polarization effect despite low humidity, resulting in highly sensitive properties in the dynamic humidity range. This model can be widely implemented in various industrial fields.